2012
DOI: 10.3892/ijmm.2012.1079
|View full text |Cite
|
Sign up to set email alerts
|

Icariin promotes bone formation via the BMP-2/Smad4 signal transduction pathway in the hFOB 1.19 human osteoblastic cell line

Abstract: Icariin, the main active compound of the traditional Chinese medicine, Epimedium, is commonly used for the clinical treatment of osteoporosis. However, the precise molecular mechanism of the therapeutic effect of icariin has not been elucidated. The aim of this study was to examine the effect of icariin on cell viability, alkaline phosphatase (ALP) activity, the amount of calcified nodules, and to delineate the molecular mechanism of icariin-enhanced bone formation by investigating the expression of bone morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 25 publications
4
73
0
Order By: Relevance
“…Mok et al (43) revealed that icariin exerts anabolic effects in bone, possibly by activating the endoplasmic reticulum in a ligand-independent manner. In previous work, we reported that icariin inhibits osteoporosis in vitro, potentially owing to its role in increasing BMP-2 protein expression (16), and that icariin promotes bone formation via the BMP-2/Smad4 signal transduction pathway in the hFOB 1.19 human osteoblastic cell line (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mok et al (43) revealed that icariin exerts anabolic effects in bone, possibly by activating the endoplasmic reticulum in a ligand-independent manner. In previous work, we reported that icariin inhibits osteoporosis in vitro, potentially owing to its role in increasing BMP-2 protein expression (16), and that icariin promotes bone formation via the BMP-2/Smad4 signal transduction pathway in the hFOB 1.19 human osteoblastic cell line (17).…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that these compounds have an anabolic effect on osteoporotic bone by concomitantly promoting the osteogenic differentiation of bone marrow stromal cells while suppressing adipogenic differentiation (13 proliferation of rat bone marrow stromal cells, increases the number that stain positive for osteocalcin (BGLAP) secretion, alkaline phosphatase (ALP) and enhances ALP activity, and calcium deposition levels in a dose-dependent manner (14,15). In previous work, we reported that icariin inhibits osteoporosis in vitro, potentially owing to its role in increasing bone morphogenetic protein-2 (BMP-2) protein expression (16), and that icariin promotes bone formation via the BMP-2/Smad4 signal transduction pathway in the hFOB 1.19 human osteoblastic cell line (17). The present study investigated whether icariin promotes bone fracture healing in ovariectomized osteoporotic (OVX) rats in vivo, with the intention of determining a novel method to treat osteoporosis-associated fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Total flavones of Epimedium (TFE) inhibited reduction of procollagen type I N-terminal propeptide (PINP), and increased serum osteocalcin and type I collagen in OVX rats (13,14). Icariin, one of the major components of Herba Epimedium, decreased activities of serum tartrate-resistant acid phosphatase (TRAP) and bioactive components could stimulate the proliferation, differentiation and mineralization of osteoblasts (12,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), suppress the adipogenesis of bone marrow-derived mesenchymal stem cells (BMSCs) (41)(42)(43)(44), inhibit the proliferation and differentiation of osteoclasts (45)(46)(47), and induce apoptosis and cell cycle arrest and suppress bone resorption of osteoclasts (48). In addition, icariin was found to significantly attenuate oxidative stress and apoptosis and preserve viability and osteogenic potential of osteoblasts exposed to hypoxia, which indicated that its anti-osteoporotic effect might be attributed to its anti-hypoxic activity (49).…”
Section: In Vivo Findingsmentioning
confidence: 99%
“…Taken together, the following pathways were involved in the osteogenesis effect of Herba Epimedium and its constituents: i) activate extracellular-signalregulated kinase (ERK), p38, c-Jun N terminal kinase (JNK)/MAPK pathways in rat BMSCs (50), ii) through ER-mediated ERK and JNK signal activation in MC3T3-E1 osteoblastic cell line (51) (34), vi) involve the ERα-Wnt/β-catenin signaling pathway in rat BMSCs (38), vii) through up-regulation of transforming growth factor (TGF)-β1, BMP2 expression in rabbit BMSCs (30), through up-regulation of BMP2 and Runx2 mRNA expression in calvarial osteoblasts from pups (13), viii) via Notch signaling pathway in rat BMSCs (53), ix) increase OPG and the OPG/RANKL ratio in UMR-106 osteoblastic cells (12), and x) stimulate ER-dependent osteoblastic functions and activate ER in a ligand-independent manner in UMR-106 osteoblastic cells (24,39).…”
Section: In Vivo Findingsmentioning
confidence: 99%
“…BMP-2, a member of the TGF-β superfamily, is a key signaling component in osteoblast proliferation and differentiation (13,14). SMAD family member 5 (Smad5) is a downstream transcription factor that is phosphorylated and activated by the receptors of BMP-2.…”
Section: Introductionmentioning
confidence: 99%